2017
DOI: 10.1186/s13046-017-0531-3
|View full text |Cite|
|
Sign up to set email alerts
|

Dihydroartemisinin inhibits TCTP-dependent metastasis in gallbladder cancer

Abstract: BackgroundPatients with metastatic or relapsed gallbladder cancer generally have a poor prognosis. Therefore, targeting metastasis is one arm of therapeutic strategies to treat gallbladder cancer.MethodsLevels of translationally controlled tumor protein (TCTP) were measured in samples of gallbladder cancer by immunohistochemical staining. Wound healing, migration and invasion assays were used to investigate the motility of cells. Western blot assay was used to investigate the levels of TCTP and other proteins.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
55
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 37 publications
2
55
2
Order By: Relevance
“…The data demonstrated that DHA synergizes with rapamycin and promotes cell death and apoptosis via the upregulation of DAPK and Atg7, which provides an indication for its usefulness in anticancer studies and clinical application. In accordance with the results of other studies regarding DHA, the effects of DHA on autophagy were further confirmed (28)(29)(30)(31)(32). The present study provides novel evidence regarding the effects of rapamycin combined with DHA and Atg7 knockdown; however, owing to the limitations of in vitro experiments, the associated combined effects should be investigated in in vivo animal models in the future, with further cell lines investigated.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The data demonstrated that DHA synergizes with rapamycin and promotes cell death and apoptosis via the upregulation of DAPK and Atg7, which provides an indication for its usefulness in anticancer studies and clinical application. In accordance with the results of other studies regarding DHA, the effects of DHA on autophagy were further confirmed (28)(29)(30)(31)(32). The present study provides novel evidence regarding the effects of rapamycin combined with DHA and Atg7 knockdown; however, owing to the limitations of in vitro experiments, the associated combined effects should be investigated in in vivo animal models in the future, with further cell lines investigated.…”
Section: Discussionsupporting
confidence: 90%
“…Zhang et al (30) demonstrated that DHA can inhibit translationally controlled tumor protein (TCTP)-dependent cell migration and invasion by inhibiting TCTP and reducing cell division control protein 42 homolog (Cdc42) activation in the TCTP-positive cell lines NOZ, GBC-SD, OCUG-1 and EH-GB-1 in vitro. Additionally, this was also demonstrated in gallbladder cancer xenograft animal models established using a spleen-to-liver metastasis model in immunodeficient mice (30). Lemke et al (31) revealed that DHA exerted an anti-glioma activity, which included promotion of autophagy and induction of oxidative stress in the glioma cell lines LN-229 and LN-Z308 as well as in the primary T269 glioma cell line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dihydroartemisinin (DHA), an antimalarial drug derivative from artemisinin, was reported own powerful anticancer effect on numerous kinds of cancers in vitro and in vivo, such as prostate cancer [8], ovarian cancer [9,10], cervical cancer [11], gallbladder cancer [12] and gastric cancer [13]. In esophageal cancer, Jiang and coauthors [14] reported that DHA performed a powerful anticancer effect toward EC cell lines Eca109 and Ec9706 in vitro and in vivo.…”
mentioning
confidence: 99%
“…Interestingly, TCTP not only induces multi-malignant cancer phenotypes but also confers chemo-and irradiation-resistance in various types of cancer by regulating oncogenic signaling such as the EGFR-AKT pathway [29][30][31][32] . Thus, clinically applicable agents that could target TCTP, such as dihydroartemisinin (DHA), rapamycin, sertraline, and thioridazine, were suggested to regress cancer [33][34][35][36] . Although the importance of TCTP as a therapeutic target continues to grow, the potential relationship between TCTP and immunotherapeutic resistance and the possibility of TCTP as a novel actionable target for combination strategies to reverse the immunotherapeutic resistance have not been explored.…”
mentioning
confidence: 99%